2007
DOI: 10.1073/pnas.0605701104
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule agonists for the glucagon-like peptide 1 receptor

Abstract: The peptide hormone glucagon-like peptide (GLP)-1 has important actions resulting in glucose lowering along with weight loss in patients with type 2 diabetes. As a peptide hormone, GLP-1 has to be administered by injection. Only a few small-molecule agonists to peptide hormone receptors have been described and none in the B family of the G protein coupled receptors to which the GLP-1 receptor belongs. We have discovered a series of small molecules known as ago-allosteric modulators selective for the human GLP-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
205
2

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 198 publications
(218 citation statements)
references
References 51 publications
6
205
2
Order By: Relevance
“…In addition, Boc5 and S4P largely, but not completely, displaced labeled GLP-1 from GLP-1R and may, therefore, also interact with the TMD (27). In contrast, the pyrimidine BETP (31) was not competed by exendin(9 -39) or GLP-1 and is, therefore, thought to allosterically activate GLP-1R (31)(32)(33)(34). Recent work has demonstrated that BETP functions by forming covalent adducts with Cys-347 in the intracellular loop 3 (ICL3) of GLP-1R, which may mimic a physiological covalent modification (35).…”
Section: Small Molecule Glp-1r Modulators Mimic Endogenous Peptide Homentioning
confidence: 99%
“…In addition, Boc5 and S4P largely, but not completely, displaced labeled GLP-1 from GLP-1R and may, therefore, also interact with the TMD (27). In contrast, the pyrimidine BETP (31) was not competed by exendin(9 -39) or GLP-1 and is, therefore, thought to allosterically activate GLP-1R (31)(32)(33)(34). Recent work has demonstrated that BETP functions by forming covalent adducts with Cys-347 in the intracellular loop 3 (ICL3) of GLP-1R, which may mimic a physiological covalent modification (35).…”
Section: Small Molecule Glp-1r Modulators Mimic Endogenous Peptide Homentioning
confidence: 99%
“…Compound 2 significantly increases glucose-stimulated insulin release from wild-type mouse pancreatic islets and from perfused rat pancreas, although not from GLP-1 receptor knockout mouse islets. It is not particularly potent, and its oral bioavailability is not reported (2). However, these findings suggest that this class of compound may be a useful starting point for the design of further drugs based on the GLP-1 signaling system.…”
mentioning
confidence: 95%
“…The chemical compound analyzed in more detail, referred to as ''compound 2,'' not only agonizes the GLP-1 receptor, but also increases its binding affinity for GLP-1. The mechanism is unknown, although it appears that binding is allosteric, and Knudsen et al (2) suggest that it may stimulate receptor dimerization. Compound 2 significantly increases glucose-stimulated insulin release from wild-type mouse pancreatic islets and from perfused rat pancreas, although not from GLP-1 receptor knockout mouse islets.…”
mentioning
confidence: 99%
See 2 more Smart Citations